Microglia positron emission tomography and progression in multiple sclerosis: thalamus on fire - Zeydan, Burcu; Neyal, Nur; Son, Jiye; Schwarz, Christopher G; Kendall; Thomas June C; Morrison, Holly A; Bush, Melissa L; Reid, Robert I; Przybelski, Scott A; Fought, Angela J; Jack, Clifford R; et al. (Oxford University Press (OUP), 2025)
Increased innate immune activity promotes neurodegeneration and contributes to progression in multiple sclerosis. This prospective case-control study aims to investigate thalamic microglia density on 18kDa translocator protein PET in patients with multiple sclerosis using a third-generation radioligand, C-11-ER176, and investigate the associations of C-11-ER176 PET uptake with imaging and clinical measures of progression in multiple sclerosis. Patients with multiple sclerosis (n = 50) and controls (n = 55) were prospectively enrolled and they underwent C-11-ER176 PET and MRI including diffusion MRI with neurite orientation dispersion and density imaging. Disease characteristics, expanded disability status scale and multiple sclerosis functional composite scores were obtained in patients with multiple sclerosis. Age at imaging (mean +/- standard deviation: patients = 49.6 +/- 12.9 years, controls = 48.2 +/- 15.4 years, P = 0.63) and sex (female ratio; patients = 72%, controls = 65%, P = 0.47) were not different between the groups. Thalamus C-11-ER176 PET uptake was highest in patients with progressive multiple sclerosis (1.272 +/- 0.072 standardized uptake value ratio), followed by patients with relapsing multiple sclerosis (1.209 +/- 0.074 standardized uptake value ratio) and lowest in controls (1.162 +/- 0.067 standardized uptake value ratio, P < 0.001). Patients with thalamic lesions had higher thalamus C-11-ER176 PET uptake than those without thalamic lesions in both relapsing multiple sclerosis and progressive multiple sclerosis (P < 0.001). In patients with multiple sclerosis, higher thalamus C-11-ER176 PET uptake correlated with lower thalamic volume (r = -0.45, P = 0.001), higher mean diffusivity (r = 0.56, P < 0.001), lower neurite density index (r = -0.43, P = 0.002), lower orientation dispersion index (r = -0.40, P = 0.005) and higher free water fraction (r = 0.42, P = 0.003) in the thalamus. In patients with multiple sclerosis, higher thalamus C-11-ER176 PET uptake also correlated with higher mean diffusivity (r = 0.47, P < 0.001) and lower neurite density index (r = -0.36, P = 0.012) in the corpus callosum. In patients with multiple sclerosis, higher thalamus C-11-ER176 PET uptake correlated with worse expanded disability status scale scores (r = 0.33, P = 0.02), paced auditory serial addition test scores (r = -0.43, P = 0.003) and multiple sclerosis functional composite z-scores (r = -0.46, P = 0.001). Microglia density in the thalamus is highest in patients with progressive multiple sclerosis and is associated with imaging biomarkers of neurodegeneration and clinical disease severity. As a signature imaging biomarker of progression in multiple sclerosis, effectively reflecting the global disease burden, C-11-ER176 PET may aid development and efficacy evaluation of therapeutics targeting microglia.